Language, gender and sexuality - Yoong, Melissa (Routledge, 2018)
This chapter reviews early research that looked for differences between women’s and men’s language use, before turning to social-constructionist perspectives based on Butler’s model of performativity. Related key theoretical advances are explored, including Ochs’s theory of indexicality, Eckert and McConnell-Ginet’s concept of the Community of Practice, and Sunderland’s notion of gendered discourses. The chapter then discusses two crucial lines of inquiry within scholarly work applying these contemporary theoretical frameworks: how women leaders negotiate their professional identities through the use of language, and the various ways masculinities are linguistically constructed and inflected by sexuality. The subsequent section explores two key areas of debate: the interactional salience of gender, and the use of the masculine/feminine dichotomy in the analysis of speech styles. The final section discusses areas of research that require further attention in the field of language and gender, including the linguistic construction of postfeminist subjectivities, and the interplay between language, gender and sexual identities that have been typically perceived as deviant. It also emphasizes the need for the field to feed research findings into practices within and beyond academia to increase social impact, and continue developing a more international perspective and ensuring intersectionality is fully taken into consideration.